Diversifikasi Produk Olahan Jeruk Nipis sebagai Upaya Peningkatan Pendapatan Kelompok Wanita Makmue Beujaya - Nasution, Anisah; Triantoro, Dony Arung; Safrika; Muzammil, Abdul; Siringo-ringo, Liston (Jurnal Pemberdayaan Masyarakat, 2025)
The Makmue Beujaya Women Entrepreneurship Group (KWW) has great potential in developing a lime-based business in Kuta Makmue Village, Nagan Raya Regency. Previously, the planted limes were only processed into one product, namely dish soap. This resulted in limited group income because the products produced were not optimal in fully utilizing the potential of lime. To overcome this problem, a community service program was implemented with the aim of encouraging the diversification of processed lime products, including by producing new products such as hand sanitizer and lime slice. This program uses the Participatory Action Research (PAR) method, which involves women group members actively in the entire process, starting from the socialization, training, to evaluation stages. The results of this activity show an increase in the capacity of women's groups, both in creating innovative products based on local potential and increasing knowledge and skills in product diversification. This effort is expected to encourage sustainable economic growth for the group and improve family welfare through a flexible business that can be done from home